23 Use of a polymer-free biolimus A9 drug-coated stent in des-type patients who are poor candidates for prolonged DAPT. (24th April 2016) - Butt, Mehmood; Abdul, Fairoz; Yazji, Khaled; Ossei-Gerning, Nick; Chase, Alex; Smith, Dave; Anderson, Richard; Kinnaird, Tim
Abstract : Background: Prolonged DAPT is undesirable in some patients. A biolimus-A9 drug-coated stent (BA9-DCS) has a rapid drug-elution profile potentially allowing shortened DAPT. Methods: Data were gathered prospectively for 410 patients deemed to be at high risk of bleeding treated with a BA9-DCS stent at 2 UK centres and compared to usual PCI patients. Results: BA9-DCS indications included warfarin therapy, age and anaemia. Patients receiving a BA9-DCS were older (71.6 ± 11.8 vs. 64.8 ± 11.6yrs, p < 0.001), more often female (38.2 vs. 26.8%, P < 0.001) and to have comorbidity including hypertension, chronic kidney disease or poor LV function than usual PCI patients. The baseline Mehran bleed risk score was also significantly higher in the BA9-DCS group (19.4 ± 8.7 vs. 13.1 ± 5.8, p < 0.001). Of the BA9-DCS cohort, 95.5% of patients demonstrated disease fitting NICE criteria for DES eligibility. The number of lesions treated (1.81 ± 1.1 vs. 1.58 ± 0.92, p = 0.003), total lesion length (32.1 ± 21.7 vs. 26.1 ± 17.6mm, p < 0.001), number of stents used (1.93 ± 1.11 vs. 1.65 ± 1.4, p-0.007) and total stent length (37.5 ± 20.8 vs. 32.4 ± 20.3, p < 0.01) were greater for BA9-DCS patients. DAPT was prescribed for 3.3 ± 3.9 months for BA9-DCS patients and 11.3 ± 2.4 months for usual PCI patients (p < 0.001). At follow up of 392 ± 124 days event rates were low with ischemia-driven restenosis PCI occurring in 6 patients (2.4%), definite/probable stent thrombosis in 2 patients (0.8%) and death in 13 patients (5.2%). Conclusions: Early outcomes using polymer-free BA9 drug-coated stents are encouraging. Further studies are warranted.